PERANAN FEEDBACK DALAM MENGOPTIMALKAN PELATIHAN PENUGASAN REVIEW PENGENDALIAN INTERN: EKSPERIMEN DENGAN KERANGKA TEORI KOGNITIF - Nurim, Yavida; Kusuma, Indra Wijaya; Supriyadi, Supriyadi; Nahartyo, Ertambang (UI Scholars Hub, 2015)
Based on cognitive theory, this study aims to compare between outcome feedback and explanatory feedback in the acquiring of internal control review task knowledge and performance. Both of feedbacks serve different review mechanism, so it will influence auditor’s judgment process. This study uses experimental method, involving undergraduate accounting students as participants as a proxy for inexperienced auditors. The result implies that training should enhance the optimum knowledge acquisition because the appropriateness of training method will encourage optimum auditor’s performance in internal control review.